Influence of Additives on Fabrication and Release from Protein Loaded Microparticles: Protein loaded microparticles - Yagnesh Bhatt; Dushyant Shah (Iranian Journal of Pharmaceutical Sciences, 2012)
The purpose of this study was to investigate the effect of additives, poly(ethylene glycol) (PEG) 1450, poloxamer 407, polyvinyl alcohol (PVA) and sodium chloride in order to improve physico-chemical characteristics, encapsulation efficiency and in vitro release of bovine serum albumin, form poly(D,L-lactic-co-glycolic acid) (PLGA) microparticles prepared by the w/o/w solvent evaporation method. The addition of PEG 1450 and 0.05 M NaCl changed the surface characteristics of microparticles and also affected the encapsulation efficiency and burst release of protein. The effect of surfactants: polyvinyl alcohol and poloxamer 407 used in the outer water phase was investigated. The surfactant/PLGA mass ratio played an important role in the preparation procedure of the particles. This ratio was found to be approximately 0.5 for PVA and 5 for poloxamer 407 in order to achieve microparticles with narrow size distribution (<70 μm) and good encapsulation efficiency (>70%).